Risky business: Comparative approaches to risk and resilience in arid environments of the Holocene – An introduction to the special issue. (December 2022) - Dawson, Emily; Weinberg, Camille; Damick, Alison
Drylands are diverse and dynamic ecosystems that have been occupied by humans throughout the Holocene. Nonetheless, drylands are often conceived of as marginal, rare, and inimical to human livelihoods. This Special Issue interrogates the interactions between humans and arid and aridifying environments to investigate how drylands offer unique risks and opportunities to their resilient inhabitants. This article introduces the 11 environmental archeology papers and 1 discussion paper in this Special Issue, the proceedings of a 2021 virtual workshop on the topics of risk and resilience. Each contribution explores a different geographic and chronological context around the globe. We also introduce three subthemes of this Special Issue: "Multi-Scalar Analysis, " "Abundance and Diversity, " and "Cascading Risks." Collectively, a key strength of the case studies in this volume is the range of environmental archeology methods and datasets that they showcase. These authors draw out details within a multi-scalar understanding of risk and risk perception in the particular contexts in which they work. As we face compounding contemporary risks associated with the global impacts of a changing climate, it is more important than ever to recognize the range of human relationships with aridification, and the dynamic, localized socio-environmental histories of drylands.